Evaluation of Library Collection of Palli Samgathana Vibhaga Library, Visva-Bharati: A Survey - Sinha, Atanu Kumar (Journal of Information and Knowledge, 2015)
Library is a service organization which requires constant assessment of its services with a vast amount of information collected on expenditure, books added and journals subscribed, books and journals issued, etc. To build a balanced and usable collection is the most important aspect of any library service which requires evaluation to see whether the users are satisfied with the library collection or not. This article gives a brief profile of Palli Samgathana Vibhaga Library, Visva- Bharati and evaluates the various factors of library collection by administering questionnaires to its users. On the basis of the data obtained, suggests some measures to enhance efficient use of the library collection and give some proposals to overcome the impediments of collection development.